Analisis Performansi VOIP (Voice Over Internet Protocol) Pada Jaringan Wimax (Worldwide Interoperability For Microwave Access) Di Wilayah DKI Jakarta - Widhiatmoko Widhiatmoko; Hesti Susilawati; Rahmat K. Noviandono (JURNAL INFOTEL, 2011)
VoIP is a system that uses the Internet network to transmit voice packets from one place to another using IP protocols intermediaries. With VoIP technology can be much cheaper call charges, especially for communicating overseas because of voice and data using the same network ie the Internet network. VoIP is a service that is very susceptible to delay while the existing access network is currently providing a significant delay for VoIP. One alternative network that can be used to overcome these problems is to use WiMAX technology because WiMAX can provide speed data services up to 70 Mbps.From the research, results of one way delay, jitter and packet loss still at the value recommended by ITU-T, which is the maximum value of one way delay measurement is 159.87 ms, for jitter 7.52 ms and for packet loss is 3.175%. The one way delay and packet loss from the measurement used to find the MOS score which is the value for quality of VoIP. MOS value range obtained from the calculation of 3.6 to 4.2, which means VoIP feasible to apply to the WiMAX network. The maximum value can reach 2.8 Mbps throughput to 0.575 Mbps for downlink and uplink. From the research also found that the SQI values that are above the standard value of the device will provide a high SNR value, and the higher SQI values then its RSSI value is also bigger.